Effect of Zn0·17Nb0·33Ti0·5O2 on the microwave dielectric properties of ZnTiNb2O8 ceramics. Issue 5 (1st March 2022) - Zhou, Guohui; Wang, Dawei; Zhu, Hai-ou; Bian, Wenjie; Gu, Huidong; Zhu, Haikui; Wang, Lixi; Zhang, Qitu; Ta, Shiwo
Abstract: An original (1-x)ZnTiNb2 O8 -xZn0.17 Nb0 · 33 Ti0 · 5 O2 (x = 0.35–0.75) composite ceramics were prepared by the traditional solid-state method. X-Ray diffraction and Raman spectroscopy results illustrated that only ZnTiNb2 O8 and Zn0 · 17 Nb0 · 33 Ti0 · 5 O2 were synthesized without any extra phase. The morphology and microstructures of the microwave dielectric ceramics were characterized by scanning electron microscopy and energy disperse spectroscopy. The addition of Zn0 · 17 Nb0 · 33 Ti0 · 5 O2 not only effectively adjusted the τ f of ZnTiNb2 O8 matrix from −39.55 ppm/°C to 54.32 ppm/°C, but also significantly increased εr from −39.55 ppm/°C to 54.32 ppm/°C. But the Q ×  f values deteriorated from 36, 914 GHz to 21, 077 GHz as x increased. The ceramic with near-zero τ f was synthesized at x = 0.55, meanwhile, 0.45ZnTiNb2 O8 -0.55Zn0 · 17 Nb0 · 33 Ti0 · 5 O2 ceramic sintered at 1200 °C possessed attractive microwave dielectric properties: εr  = 39.08 (6.2 GHz), Q ×  f  = 31, 384 GHz, and τ f  = −6.45 ppm/°C.